Colonizing the Port City Pusan in Korea: a study of the process of Japanese domination in the urban space of Pusan during the open-port period (1876-1910) - Kang, S (2012)
This dissertation aims to analyze the transformation of Pusan by examining the social, political, economic, and cultural changes during the open-port period (1876-1910). Prior to annexation, Pusan, as the first open port in Korea, reflected features of the colonial urban development in which alien power achieved and sustained a hegemonic domination on socio-cultural-economic dimensions of people’s lives. Colonial history in Korea has been divided and moving on parallel lines. The ‘nationalist school’ and the ‘socioeconomic school’ have failed to come together and move us into a deeper understanding of the Japanese colonial period. In order to narrow the gap between the two schools of thought, this thesis suggests looking at ‘colonial modernity’ through the analytical lens of the colonial city of Pusan. The approach examines changes in the social, economic, and cultural life of people rather than through the traditional binary construction of ‘victim versus victimizer’ or ‘colonial repression versus national resistance.’ In particular, I pay close attention to the fact that colonization is a process of imperial expansion by means of colonialists. In the end, the process of colonization in Pusan was a process by which the Japanese settlers expanded in wealth, population, influence, and power. The cluster of factors – enlargement of settlement (living space), the expansion of the economy (economic opportunity), improvement of public enterprises, such as transportation infrastructure, water supply and hygiene (improving quality of life) – were catalysts for the Japanese settlers to take up residence in Pusan. Based on the transformation of the urban space of Pusan at this micro level, I discuss a hierarchy of power relations within the spatial boundary of Pusan. In other words, I focus on human aspects of these changes rather than on systemic changes. I attempt to demonstrate how studying a city can offer a useful category of analysis for the question of ‘modernity’ in Korea.